First Record Of Rust Caused By Tranzschelia Discolor (Fuckel) Tranz. & Litv. On Stone Fruits In Jammu & Kashmir (India) (Applied Biological Research, 2014)
Stone fruit crops, comprising of apricot, cherry, peach, plum and nectarines, are widely distributed  throughout the temperate and sub-temperate regions of world. In India, they are grown in  Himalayan mountainous region mainly in the states of Jammu & Kashmir, Himachal Pradesh and  Utarakhand. In Jammu & Kashmir state the stone fruit crops are grown on 17,415 ha with annual  production of 39,160 metric tonnes (Anonymous, 2012). In July-August 2013, during a routine  disease survey of fruit orchards, the leaves of apricot, cherry, peach and plum were found affected  by an unusual disease. The leaves of infected plants developed rusty brown pustules which  manifested as small circular to angular pale yellow spots on both the leaf surfaces. The spots on  lower leaf surface developed typical cinnamon rusty brown pustules (sori) of urediniospores. Black  teliospores developed in late season among the cinnamon rusty brown urediniospores. The leaves  bearing rust pustules turned yellow or red and resulted in severe leaf defoliation (Plate 1a-c). The  twig infection although inconspicuous appeared as light water-soaked swellings bearing the  urediniospores of fungus.
Keywords: Caused; Stone; Jammu & Kashmir